Dynamic of Cytokine Storm in Human Inflammatory Response of Severe Acute Respiratory Syndrome Coronavirus (SARS-CoV)-Induced Disease. Issue 1 (March 2021) - Wiraya, A; Fitriana, L; Triyanto,; Setiawan, R
Abstract: Infection of Severe Acute Respiratory Syndrome Coronavirus (SARS-CoV) in the human body is characterized by the detection of large amounts of the virus by cytokine as the response to inflammation. In the human body, there are two types of inflammatory responses by a cytokine called pro-inflammatory and anti-inflammatory cytokine. A non-dimensionalized mathematical model of the inflammatory response system has been constructed in the form of a system of differential equations, which consists of two variables and five parameters. The rate of pro-inflammatory and anti-inflammatory cytokine natural production are two important parameters that correlate with a chronic SARS-CoV infection called a cytokine storm. Varying these parameter values, some non-chaotic torus attractors were found in some numerical simulation with the initial value around the equilibrium point obtained by fixing parameter values at the Generalized Hopf bifurcation point. These phenomena show that in cytokine storm condition, fluctuation of pro-inflammatory and anti-inflammatory cytokines form some patterns which are complex, so that they are difficult to be predicted. Mesenchymal stem cells (MSC), chloroquine (CQ), and hydroxychloroquine (HCQ), which have an effect on pro-inflammatory and anti-inflammatory cytokine production, can be used to reduce the cytokine storm.